2008
DOI: 10.1097/iop.0b013e318160744b
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Primary Optic Nerve Lymphoma

Abstract: A 69-year-old man was examined for bilateral infiltrative optic neuropathy. Optic nerve biopsy confirmed a malignant B cell lymphoma. Systemic examination and investigations failed to show involvement of other sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Alternately, our broader search leads us to conclude that the potential for both neoplastic infiltration and the predilection to cause leptomeningeal carcinomatosis/lymphoma of the anterior visual segments is considerably more common. 26-30 Systematic ascertainment has demonstrated a rate as high as 90%, 31 with a concordance rate of systemic involvement in greater than half of those with histopathologic confirmation of lymphomatous infiltration of the optic nerve. 29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternately, our broader search leads us to conclude that the potential for both neoplastic infiltration and the predilection to cause leptomeningeal carcinomatosis/lymphoma of the anterior visual segments is considerably more common. 26-30 Systematic ascertainment has demonstrated a rate as high as 90%, 31 with a concordance rate of systemic involvement in greater than half of those with histopathologic confirmation of lymphomatous infiltration of the optic nerve. 29…”
Section: Discussionmentioning
confidence: 99%
“…Alternately, our broader search leads us to conclude that the potential for both neoplastic infiltration and the predilection to cause leptomeningeal carcinomatosis/lymphoma of the anterior visual segments is considerably more common. [26][27][28][29][30] Systematic ascertainment has demonstrated a rate as high as 90%, 31 with a concordance rate of systemic involvement in greater than half of those with histopathologic confirmation of lymphomatous infiltration of the optic nerve. 29 A study involving patients with confirmed leptomeningeal carcinomatosis revealed that vision loss was the predominant ocular symptom in over 70%, while half reported that their visual disturbance was their initial and the corresponding symptom which prompted them to seek out medical attention.…”
Section: Discussionmentioning
confidence: 99%
“…41 Limitations of a medial conjunctival biopsy include obtaining only a small amount of tissue for, as well as accessing only the most anterior portion of the optic nerve. Previously reported patients who underwent optic nerve biopsy for lymphoma had no significant visual deterioration.…”
Section: Optic Nerve Biopsy Indications and Techniquesmentioning
confidence: 99%
“…To date, most reports of ONBs in the literature have been limited to single case reports and highlight the need to consider a broad differential diagnoses and to perform extensive evaluations before biopsy (2)(3)(4)(5)(6). We performed a retrospective review at a tertiary care institute to identify patients who underwent ONB.…”
mentioning
confidence: 99%